The Chlorophyll Biosynthetic Enzyme Mg-Protoporphyrin IX Monomethyl Ester (Oxidative) Cyclase (Characterization and Partial Purification from Chlamydomonas reinhardtii and Synechocystis sp. PCC 6803). - Bollivar, D. W. (1996)
A universal structural feature of chlorophyll molecules is the isocyclic ring. This ring is formed by the action of the enzyme Mg-protoporphyrin IX monomethyl ester (oxidative) cyclase, which catalyzes a complex reaction in which Mg-protoporphyrin IX monomethyl ester is converted to divinyl protochlorophyllide (also called Mg-2,4-divinylpheoporphyrin a5), with the participation of NADPH and O2. Cyclase activity was demonstrated in lysed Chlamydomonas reinhardtii chloroplasts and extracts of Synechocystis sp. PCC 6803. The yield of the reaction product was increased by the addition of catalase and ascorbate or isoascorbate to the incubation mixture. These compounds may act by preventing degradation of the tetrapyrroles by reactive oxygen species. Cyclase activity from C. reinhardtii was not inhibited by the flavoprotein inhibitor quinacrine or by the hemoprotein inhibitors CO, KCN, or NaN3. In contrast, cyclase activity in extracts of C. reinhardtii and Synechocystis sp. PCC 6803 was inhibited by chelators of Fe, suggesting that nonheme Fe is involved in the reaction. Cyclase in lysed C. reinhardtii chloroplasts was associated with the membranes, and attempts to further fractionate or solubilize the activity were unsuccessful. In contrast, cyclase in Synechocystis sp. PCC 6803 extracts could be separated into soluble and membrane components, both of which were required for reconstitution of activity. The membrane component retained activity after it was solubilized by the detergent n-octyl-[beta]-D-glucopyranoside in the presence of glycerol and Mg2+. The solubilized membrane component was purified further by dye-affinity and ion-exchange chromatography.